Design, fabrication and testing of discrete 3D sand-printed floor prototypes. (June 2018) - Rippmann, M.; Liew, A.; Van Mele, T.; Block, P.
Abstract: This paper describes the concept, design, fabrication and experimental testing of prototype 3D sand-printed floors, derived from principles of shallow arching action and discrete structural systems to initiate internal compressive stresses rather than exclusively flexural stresses. Using industrial 3D printing with silica sand, the presented system enables significant weight reduction of up to 70% when compared to conventional concrete floor slabs, by placing the 3D printed material in key structural areas and by externalising tension forces. The form-finding process for the global shape of the floors and the generation of structurally optimised print mesh geometries are presented. Three floor prototypes with varying rib geometries and discretisation layouts were studied. The results from the serviceability and ultimate load testing of the floors are documented in detail. The data showed that this relatively weak material can be used, without internal reinforcement, to print a floor that is able to support loads in excess of typical design code levels.